2016
DOI: 10.1073/pnas.1520180113
|View full text |Cite
|
Sign up to set email alerts
|

Successful immunotherapy induces previously unidentified allergen-specific CD4+ T-cell subsets

Abstract: Allergen immunotherapy can desensitize even subjects with potentially lethal allergies, but the changes induced in T cells that underpin successful immunotherapy remain poorly understood. In a cohort of peanut-allergic participants, we used allergen-specific T-cell sorting and single-cell gene expression to trace the transcriptional "roadmap" of individual CD4+ T cells throughout immunotherapy. We found that successful immunotherapy induces allergen-specific CD4+ T cells to expand and shift toward an "anergic"… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
124
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 126 publications
(134 citation statements)
references
References 56 publications
6
124
0
3
Order By: Relevance
“…The mechanisms by which mast cell and basophil responsiveness to degranulation are decreased early during immunotherapy are under investigation 76 . Other changes to the immune system observed after immunotherapy include increased numbers of anergic antigen-specific T cells 77 , apoptotic antigen-specific T cells 7881 and FOXP3 + T reg cells 80,82 , as well as increased levels of TGFβ1 (REFS 77,83). For example, over the course of OIT, antigen-specific CD4 + T cells were found to transition from allergic and regulatory phenotypes to anergic and non-allergic phenotypes, in association with decreased allergic symptoms and the development of sustained unresponsiveness 77 .…”
Section: Immune Mechanismsmentioning
confidence: 99%
“…The mechanisms by which mast cell and basophil responsiveness to degranulation are decreased early during immunotherapy are under investigation 76 . Other changes to the immune system observed after immunotherapy include increased numbers of anergic antigen-specific T cells 77 , apoptotic antigen-specific T cells 7881 and FOXP3 + T reg cells 80,82 , as well as increased levels of TGFβ1 (REFS 77,83). For example, over the course of OIT, antigen-specific CD4 + T cells were found to transition from allergic and regulatory phenotypes to anergic and non-allergic phenotypes, in association with decreased allergic symptoms and the development of sustained unresponsiveness 77 .…”
Section: Immune Mechanismsmentioning
confidence: 99%
“…Moreover, sustained nonresponsiveness to peanut, even after a 3-month period of withdrawal from peanut, was associated with induction and maintenance of naïve and memory peanut-specific T cells that were detectable even 3 months after therapy. 172 The failure to maintain tolerance to the offending allergen may be due to the induction of Tregs that are short lived or epigenetically modified. In our cohort of subjects who completed 24 months of peanut OIT (20/23 subjects), we have shown that 7/20 subjects were still “immune tolerant” after a 3 month period of withdrawal, and 3/7 remained “immune tolerant” after an additional 3 month withdrawal period (totaling 6 months of withdrawal from therapy).…”
Section: Immunotherapy: Mechanisms Of Desensitization and Long-term Tmentioning
confidence: 99%
“…159 A major strength is that it allows the assessment of approximately 100 gene transcripts within a single cell by selecting specific genes for study or else many thousands of transcripts by using genome-wide analyses with single-cell RNAsequencing. 160 Other single-cell platforms now enable functional assays of a single cell in vitro .…”
Section: Future Directions and Clinical Implicationsmentioning
confidence: 99%